Nationalism, Social Theory and Durkheim - Dingley, J. author. aut Link
VI, 236 p.
Keywords: Ethno-national and religious identity and violence dominate modern politics, from Northern Ireland to terrorism in Sri Lanka, the former Yugoslavia or Afghanistan and Iraq. This book shows that social theory should be a major tool in helping explain national, religious and identity problems.